The Development of Flipped Classroom Learning Design Assisted by Digital Storytelling Media in the Photography Course for Visual Communication Design Students in The Bachelor's Program at STIE Asia Malang - Fathurrosi; Ulfa , Saidah; Degeng, Made Duananda Kartika (ETERNAL (English Teaching Journal), 2024)
This study aims to develop a flipped classroom instructional design assisted by digital storytelling media for the Photography course for undergraduate students of Visual Communication Design at STIE Asia Malang. The approach of project-based learning integrates the use of technology and active learning methods to enhance the effectiveness of learning. The Research and Development design used the instructional design proposed by Degeng & Degeng (2018). It divided into three phases of instructional design formation, namely 1) analysis of learning conditions, 2) development of learning strategies, 3) development of outcome measurement procedures. The results of the study show that this instructional design is effective in increasing student engagement and active participation. Students are more involved in the learning process, more motivated, and better able to apply the knowledge they have gained in real projects. Additionally, their learning outcomes significantly improved in both conceptual understanding and practical application. The efficiency of this design is also evident from the optimization of learning time, where students can utilize out-of-class time to study the materials, while in-class time is used for more interactive discussions and collaborative projects.